Peranan p53 dalam perkembangan dan prognosis osteosarkoma: tinjauan pustaka - I Wayan Juli Sumadi; Nyoman Adiputra (DiscoverSys Inc., 2020)
Background: Osteosarcoma is the most common non hematopoietic primary malignant tumor in the bone. Several factors have been related through the development and prognosis of osteosarcoma. One of them is the mutation of p53 gene that encodes p53 protein. This literature review aims to evaluate the role p53 in the progressiveness and prognosis of osteosarcoma.Methods: A review of relevant literature was performed to elaborate p53 involvement in osetosarcoma. A total of 22 qualified published literature from 2006 until 2017 were collected from several electronic database as well as manual search and included in this review.Results: P53 has an important role in maintaining genome integrity through its ability to induce genes involved in senescence process, DNA repair and apoptosis. Loss of P53 induces progenitor cells to proliferate and experience differentiation disturbances thereby increasing the potential malignant transformation to osteosarcoma. Loss of p53 also increases osteosarcoma progression by increasing proliferation and providing a good microenvironment for tumor cells. P53 causes inhibition to other tumor suppressor proteins such as BMP-2 and CD137L. Loss of P53 has a role in providing a good microenvironment for osteosarcoma cells to invade surrounding tissue, metastasis and suppressed immune response through increased activity of SDF-1, HIF-1Î±, VEGF, and NO. High mutant p53 expression has a positive association with short-term survival but does not have a strong association to predict long-term survival.Conclusion: A p53 gene has a pivotal role in the progressiveness and prognosis of osteosarcoma through increasing proliferation and providing a good microenvironment for tumor cellsÂ Latar Belakang: Osteosarkoma merupakan tumor ganas primer non hematopoietik tersering pada tulang. Berbagai faktor telah dikaitkan dengan perkembangan dan prognosis pasien osteosarkoma, Salah satunya adalah mutasi gen p53 yang menyandi protein p53. Tinjauan pustaka ini bertujuan untuk mengevaluasi peran p53 dalam progresif dan prognosis osteosarkoma.Metode: Tinjauan pustaka yang relevan dilakukan untuk menguraikan keterlibatan p53 dalam osetosarcoma. Sebanyak 22 literatur yang diterbitkan berkualitas dari 2006 hingga 2017 dikumpulkan dari beberapa basis data elektronik serta pencarian manual dan dimasukkan dalam ulasan ini.Hasil: P53 mempunyai peranan yang sangat penting dalam menjaga integritas genom melalui kemampuannya untuk menginduksi gen-gen yang terlibat dalam proses penuaan sel, perbaikan DNA maupun apoptosis. Hilangnya p53 menginduksi sel-sel progenitor osteosarkoma untuk berproliferasi dan mengalami gangguan diferensiasi sehingga meningkatkan potensi transformasi keganasan menjadi osteosarkoma. Kehilangan p53 juga meningkatkan progresivitas osteosarkoma melalui peningkatan proliferasi dan penyediaan lingkungan mikro yang baik bagi sel tumor. P53 menyebabkan hambatan fungsi protein penekan tumor lainnya yaitu BMP-2 dan CD137L. Kehilangan p53 berperan dalam menyediakan lingkungan mikro yang baik untuk sel-sel osteosarkoma untuk menginvasi jaringan sekitar, bermetastasis dan menghambat aktivitas sistem imun melalui peningkatan aktivitas SDF-1, HIF-1Î±, VEGF, dan NO. Ekspresi p53 mutan yang tinggi memiliki hubungan positif dengan angka harapan hidup jangka pendek namun tidak memiliki hubungan yang kuat untuk memprediksi harapan hidup jangka panjang.Kesimpulan: Gen p53 memiliki peran penting dalam progresivitas dan prognosis osteosarkoma melalui peningkatan proliferasi dan menyediakan lingkungan mikro yang baik untuk sel tumor.